S-phase-specific radiosensitization by gemcitabine for therapeutic carbon ion exposure in vitro - Harrabi, Semi B.; Adeberg, Sebastian; Winter, Marcus; Haberer, Thomas; Debus, Jürgen; Weber, Klaus-Josef (Journal of radiation research, 2016)
Abstract. Densely ionizing charged particle irradiation offers physical as well as biological advantages compared with photon irradiation. Radiobiological dat
Gesehen am 02.03.2020